Entlang des Weges gesät - doch nicht vergebens!: eine Notiz zu Mk 4,4 im Licht von Mk 10,46 - Lau, Markus (Biblische Notizen, 2009)
The article points to the intratextual connection between Mk 4,4.15 and 10,46, which is established through the expression para. th.n o`do,n. Against this backdrop, the parable of the Sower (Mk 4,1-9) is read as a story of hope with regard to the spread of God’s word. According to Mk 10,46 even a grain sowed on the side of the way is not automatically doomed or lost (in contrast to the logic of Mk 4,4.15). The faithful Bartimäus sitting on the side of the way is the literary example of this.